2001
DOI: 10.1097/00000542-200108000-00029
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of Low-dose Lidocaine in a Rat Model of Transient Focal Cerebral Ischemia

Abstract: The current study demonstrated that a clinical anriarrhythmic dose of lidocaine, when given before and during transient focal cerebral isehemia, significantly reduced infaret size, improved neurologic outcome, and inhibited postisehemic weight loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(49 citation statements)
references
References 29 publications
2
46
0
1
Order By: Relevance
“…The administration of progesterone before 2 hours of ischemia and after 48 hours of reperfusion was responsible for a smaller weight loss 24 . The administration of lidocaine before ischemia followed by 7 days of reperfusion caused a lower weight loss on treated animals than in controls 25 . The weight reduction observed in the present study may be attributed to the surgical procedure and to anesthesia.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The administration of progesterone before 2 hours of ischemia and after 48 hours of reperfusion was responsible for a smaller weight loss 24 . The administration of lidocaine before ischemia followed by 7 days of reperfusion caused a lower weight loss on treated animals than in controls 25 . The weight reduction observed in the present study may be attributed to the surgical procedure and to anesthesia.…”
Section: Discussionmentioning
confidence: 85%
“…Variations in body weight have been used in recent studies as a parameter to evaluate transitory focal cerebral ischemia 24,25 . The administration of progesterone before 2 hours of ischemia and after 48 hours of reperfusion was responsible for a smaller weight loss 24 .…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Table 3, administration of lidocaine ameliorates the electrophysiological activities and reduces infarct volume during focal ischemia. Lei et al (2001) reported that continuous administration of lidocaine at a clinical dose reduced cerebral infarct size at 48 h and 7 days after MCA occlusion, improved neurologic outcome, and inhibited post-ischemic weight loss in rats. As shown in Table 4, administration of lidocaine has been reported to delay the onset of depolarization (Ayad et al, 1994;Liu et al, 1997;Raley-Susman et al, 2001;Seyfried et al, 2005), reduce the amplitude of negative DC deflection (Ayad et al, 1994;Raley-Susman et al, 2001), and facilitate the recovery of membrane potential from depolarization (Weber and Taylor, 1994;Niiyama et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In 2 randomized, double-blinded, prospective clinical studies, continuous administration of lidocaine significantly ameliorated postoperative cognitive dysfunction in patients undergoing cardiac surgery for left heart valve procedures (Mitchell et al, 1999) or coronary artery bypass surgery with cardiopulmonary bypass (Wang et al, 2002). In animal models of ischemia, administration of lidocaine has been shown to ameliorate cognitive dysfunction (Popp et al, 2011) and reduce infarct volume (Shokunbi et al, 1990;Lei et al, 2001Lei et al, , 2004. Sodium entry and loss of membrane potential comprise some of the first steps in the development of ischemic neuronal damage.…”
Section: Introductionmentioning
confidence: 99%
“…The local anesthetic lidocaine may provide some added benefit through its ability to block the Na + channel, reduce Na + K + transmembrane flux, and decrease basal energy expenditures. 15 Usually 1 to 2 mg/kg of lidocaine may be given as an intravenous bolus immediately prior to the ischemic event. Most effective neuroprotective techniques used today involve some combination of the above therapies associated with some level of hypothermia, which still seems to be the most effective for neural protection during periods of transient forebrain ischemia.…”
Section: Neurosurg Focus / Volume 12 / May 2002mentioning
confidence: 99%